Dual-Energy X-Ray Absorptiometry and Anthropometry for Assessment of Nutritional Status at Diagnosis in Children with Cancer: A Single-Center Experience from India - Priyanka, Soni; Sandeep, Jain; Gauri, Kapoor; Gayatri, Vishwakarma (South Asian Journal of Cancer, 2022)
Background The survival of children with cancer has improved owing to advances in chemotherapy and better supportive care, and nutritional support is an important component of the latter especially in low- and middle-income countries like India.Materials and Methods A prospective observational study of 137 newly diagnosed children with cancer aged less than 18 years was planned. Nutritional assessment was done using dual-energy X-ray absorptiometry (DXA), anthropometry, and serum albumin. Patients were followed for 3 months for assessment of treatment-related morbidity.Results Lean body mass (LBM; DXA), mid-upper arm circumference (MUAC), and body mass index detected undernutrition in 44, 45, and 14% patients, respectively. Combination of arm anthropometry (MUAC and triceps skinfold thickness) with serum albumin categorized patients as adequately nourished (32%), moderately depleted (18%), and severely depleted (49%). Patients with hematological malignancy had a higher prevalence of undernutrition but there was no difference in morbidities between the undernourished and adequately nourished children by any parameter. Hypoalbuminemia observed in 25% patients was associated with significant chemotherapy delays (p, 0.01) and interval admissions (p, 0.03). Using LBM as a criterion, linear regression analysis revealed MUAC (R2 = 0.681) as the best predictor of undernutrition with lowest standard error.Conclusion Our study reports undernutrition among two-fifths of newly diagnosed patients of childhood cancer associated with high prevalence of sarcopenia and adiposity. These findings are of utmost clinical relevance in planning interventional strategies.
Keywords: undernutrition; arm anthropometry; LBM